Software development for prediction of projectiles’ flight path - Loh, Kee Chuan (2019)
The flight path of a person fallen from a height can be described as a projectile motion. This project aims to develop a software that is able to judge the chances of foul play in a fall to death case, with limited input data. This report shows that how to get the different parameter of a projectile motion, such as the initial velocity and falling height, through calculation with limited input data. To support more on the analysis, the falling motion such as sit-to-stand, walking, being pushed or thrown are also studied and discussed. The difference between different falling motions and the effect on the calculation has also been discussed. A simple software is developed for falling height estimation and also for analyzing the chances of foul play, based on the finding in falling motion. With a known falling height and distance, the software can determine the chances of foul play by calculating the initial horizontal velocity.